IRREGULAR MIGRATIONS AS A CHALLENGE TO REGIONAL AND NATIONAL SECURITY - Subotic, Milovan (The Policy of National Security, 2024)
After a decade-long duration of robust migratory movements towards Europe, it can be asserted that the response, in the form of a continuous disposition against migration, is primarily rooted in the perceived cultural threat. Immigrants are viewed as unassimilable, and their cultures as incompatible with Western norms and ideals. Advocacy for the preservation of Western values and culture thus becomes a tool for the exclusion and segregation of immigrants. Conservative political currents (which are increasingly gaining traction in European elections) generally argue that Europe could not withstand such an influx. More liberal politicians, however, contend that the Old Continent is sufficiently wealthy to absorb uninvited newcomers, citing Turkey’s ability to host over three million Syrian refugees and spend an average of three thousand dollars per capita on each, suggesting that the EU could afford several hundred thousand asylum seekers. It is a fact that not all impoverished individuals worldwide can solve their problems by relocating to Europe; however, it is equally factual that a more comprehensive and effective strategy aimed at globally reducing the gap between the rich and the poor might begin to address this issue better than all fences and barriers combined. The Western Balkans region mirrors European trends where the issue of irregular migration occupies a prominent position on the security agenda. Through the regional lens, a duality of problems becomes apparent, with varying degrees of equivalence concerning the broader European context. Regarding migration as a general security challenge, the salience is heightened in areas relating to the overall increase in insecurity, particularly in border areas, resulting in pronounced activities of smuggling groups, conflicts among them, and prevailing unease among the local population. An illustration of regional instability stemming from the corpus of general security challenges is analyzed through the example of the Hungarian-Serbian border. In terms of security challenges eliciting excessive responses to migration, regional circumstances markedly differ from broader European ones, for at least two reasons. The first pertains to the fluidity of the area, where migrants are still not perceived as individuals who might “take away” jobs and social protection from the local population. The second reason lies within the domain of inherited regional instability, which continues to primarily focus on antagonistic reasons stemming from the corpus of ethno-confessional “insurmountable” differences among regional actors.